Targeting genomic receptors in voided urine for confirmation of benign prostatic hyperplasia - Mathew Thakur; Vivek S. Tomar; Emma Dale; Leonard G. Gomella; Charalambos Solomides; Oleksandr Kolesnikov; Scott W. Keith; Hector T. Navarro; Olivia Dahlgren; Michael Chaga; Edouard J. Trabulsi (BJUI Compass)
Abstract Objectives The objective of this study is to validate a hypothesis that a non‐invasive optical imaging assay targeting genomic VPAC receptors on malignant cells shed in voided urine will represent either benign prostatic hyperplasia (BPH) or prostatic cancer (PCa). Risk for BPH in men 50–70 years old is 50–70% and PCa is 17%. BPH and PCa can coexist in 20% of men with BPH. Most commonly practiced methods to diagnose BPH do not distinguish BPH from PCa. Patients (or Materials) and Methods Males with BPH (N = 97, 60.8 ± 6.3 years, prostate‐specific antigen 0.7 ± 0.4 ng/mL) and without oncologic disease (N = 35, 63.4 ± 5.8 years, prostate‐specific antigen < 1.5 ng/mL) signed informed consent form and provided voided urine. Urine was cytocentrifuged, cells collected on glass slide, fixed, treated with VPAC specific fluorophore TP4303 (Kd 3.1 × 10−8M), washed, incubated with DAPI and observed using a fluorescence microscope. Cells with no VPAC did not fluoresce (BPH) and those with VPAC had red‐orange fluorescence (PCa). Real‐time polymerase chain reaction analyses for VPAC and NKX3.1 assay for cell origin were performed. Results Eighty‐seven subjects were negative for VPAC expression. Positive VPAC expression was noted in 10 subjects. Patient chart review for clinical data on these 10 VPAC positive subjects showed five had nephrolithiasis, three had renal cysts, one had prostatitis and one was being treated with finasteride. Real‐time polymerase chain reaction analysis‐VPAC expressions for 7 normal and 12 BPH subjects were 1.31 ± 1.26 and 0.94 ± 0.89, respectively (P = 0.46). NKX3.1 showed cells of prostate origin for finasteride‐treated patient. Specificity for VPAC urine assay for excluding prostate cancer in this BPH cohort was 88.5%, positive predictive value 0.00% and negative predictive value 100%. Conclusion VPAC assay may contribute extensively for BPH diagnosis and warrant continued investigation.